Generalist, selective or 'mixed' foragers? Feeding strategies of two tropical toads across suburban habitats. (9th August 2021) - Petrozzi, F.; Akani, G. C.; Eniang, E. A.; Ajong, S. N.; Funk, S. M.; Fa, J. E.; Amadi, N.; Dendi, D.; Luiselli, L.
Abstract: Suitable habitats for anurans can be found in the ever‐growing tropical urban environments but anurans' adaptations to urban conditions, including their trophic ecology remain largely unknown. We studied the food habits of two generalist, widespread West African Sclerophrys adult toads: African common ( Sclerophrys regularis ) and Hallowell's toad ( Sclerophrys maculata ). The first was studied in Lomé (Togo), Cotonou (Benin) and Ikeja (Nigeria), and the second in Port Harcourt and Ikeja (both Nigeria); the latter city represents the only studied sympatric occurrence. Mean dietary overlap between population pairs was relatively high, and diet composition of the two species when sympatric did not differ significantly. Food niche width was significantly positively correlated with local rainfall in both species, and diet composition changed significantly between the dry and wet seasons. Diversity metrics revealed that females had a more diversified diet, with higher evenness and lower dominance index values than males. The diet of both species was not correlated to prey type availability, in both the wet and dry season. Both toad species targeted specific food items rather than opportunistically consume prey as observed in most anurans which may be a response to high anuran diversity typically found in the tropics or an adjustment to urban habitats. Abstract : We studied the food habits of two generalist, widespread West African Sclerophrys adult toads: African common ( S. regularis ) and Hallowell's toad ( S. maculata ) in four distinct cities. Mean dietary overlap between population pairs was relatively high, and the diet composition of the two species when sympatric did not differ significantly. Food niche width was significantly positively correlated with local rainfall in both species, and diet composition changed significantly between the dry and wet seasons. Diversity metrics revealed that females had a more diversified diet than males. The diet of both species was not correlated with prey type availability, in both wet and dry seasons.